2006
DOI: 10.1016/j.ejcts.2005.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary blastoma — a rare tumor with variable presentation

Abstract: Pulmonary blastomas are rare tumors but can present with differing clinical features. Early detection and treatment may improve prognosis. Further larger series are needed to evaluate the characteristics of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 7 publications
0
21
0
3
Order By: Relevance
“…A study of 5 patients with CBPB by Liman et al between 1987 and 2000 demonstrated long-term survival obtained by radical surgery in patients who have small size tumor (<5 cm) without nodal involvement [20]. Another study of 7 patients between 1993 and 2004 by Adluri et al showed similar long-term survival by radical surgery in stage T2N0M0 [26]. Local recurrence has been treated successfully with surgery in a few cases [8].…”
Section: Discussionmentioning
confidence: 89%
“…A study of 5 patients with CBPB by Liman et al between 1987 and 2000 demonstrated long-term survival obtained by radical surgery in patients who have small size tumor (<5 cm) without nodal involvement [20]. Another study of 7 patients between 1993 and 2004 by Adluri et al showed similar long-term survival by radical surgery in stage T2N0M0 [26]. Local recurrence has been treated successfully with surgery in a few cases [8].…”
Section: Discussionmentioning
confidence: 89%
“…In our patient, on the basis of the presence of two important prognostic factors the biphasic pattern of the disease on IHC and the large size of the tumor on X-ray chest (PA view) and computed tomography of thorax, patient was planned for adjuvant chemotherapy following resection of the tumor. Although the long term survival of the patient with PB have been reported in several individual case reports, but the overall prognosis of the patient with PB remain to be poor, [8]. In one survey of 83 patients with PB, approximately mean survival of 33 months was reported in those patients where negative margin was achieved during surgical excision of the tumor, [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the long term survival of the patient with PB have been reported in several individual case reports, but the overall prognosis of the patient with PB remain to be poor, [8]. In one survey of 83 patients with PB, approximately mean survival of 33 months was reported in those patients where negative margin was achieved during surgical excision of the tumor, [8].…”
Section: Discussionmentioning
confidence: 99%
“…In one survey of 83 cases, the mean survival of approximately 33 months was reported for the patients who underwent surgery and achieved negative margins [13]. The factors contributing to the unfavorable prognosis are the biphasic type, tumor recurrence, metastatic disease on presentation, tumor size over 5 cm, and frequent lymph node involvement [14].…”
Section: Discussionmentioning
confidence: 99%